Genetic divergence in rapeseed-mustard (Brassica rapa L.) (Bangladesh Journal of Agricultural Research, 2013)
An experiment was conducted at the experimental farm of Sher-e-Bangla Agricultural University, Dhaka, during November 2009 to February 2010 to study the genetic divergences of 32 genotypes of Brassica rapa L. through principal component analysis and Mohalanobis D2 analysis. Analysis of variance indicated that considerable genetic variability were existed among the 32 genotypes. On the basis of D2 analysis, the genotypes were grouped into 6 clusters. Cluster III had the maximum number of 11 genotypes, while the cluster IV and cluster V had only 2 genotypes each. The highest inter-cluster distance was observed between cluster I and V (21.871), while the lowest in the cluster II and III (4.237). The intra cluster distance was the maximum in cluster V (0.469) and minimum in cluster III (0.116). The characters yield per plant, number of siliquae per plant, and days to maturity were found prominent towards the genetic divergence. The genotypes G-15 and G-19 from cluster IV and G-1, G- 3, G-4, G-10, G-18, and G-24 from cluster I were suitable for creating more variability for higher yield per plant through hybridization DOI: http://dx.doi.org/10.3329/bjar.v38i3.16968 Bangladesh J. Agril. Res. 38(3): 417-423, September 2013